2015
DOI: 10.1002/ange.201509288
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide as a Hydrogen Acceptor for the Dehydrogenative Coupling of Alcohols

Abstract: The oxidation of alcohols with N 2 Oasthe hydrogen acceptor was achieved with low catalyst loadings of arhodium complex that features ac ooperative bis(olefin)amido ligand under mild conditions.T wo different methods enable the formation of either the corresponding carboxylic acid or the ester.N 2 and water are the only by-products.M echanistic studies supported by DFT calculations suggest that the oxygen atom of N 2 Oistransferred to the metal center by insertion into the RhÀHbond of arhodium amino hydride sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…25 An alternative and high-yielding synthesis of 2b is a ligand exchange reaction whereby the PPh 3 ligand in the amide complex 2a is displaced by addition of a Nheterocyclic carbene (Scheme 2). 26 These tetra-coordinated 16 electron rhodium(I) amido complexes 2 adopt a butterfly-type geometry (that is a trigonal bipyramidal structure with one missing ligand in the equatorial plane). The rhodium centers are coordinated to two olefinic units as π-acceptors in the equatorial positions and to an amido and phosphane or N-heterocyclic carbene as ς-donor groups placed mutually trans in the axial positions.…”
Section: Introductionmentioning
confidence: 99%
“…25 An alternative and high-yielding synthesis of 2b is a ligand exchange reaction whereby the PPh 3 ligand in the amide complex 2a is displaced by addition of a Nheterocyclic carbene (Scheme 2). 26 These tetra-coordinated 16 electron rhodium(I) amido complexes 2 adopt a butterfly-type geometry (that is a trigonal bipyramidal structure with one missing ligand in the equatorial plane). The rhodium centers are coordinated to two olefinic units as π-acceptors in the equatorial positions and to an amido and phosphane or N-heterocyclic carbene as ς-donor groups placed mutually trans in the axial positions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the monomeric ruthenium‐diazadiene 14 [53] (even with double catalyst loading in order to match the metal concentration) shows some activity (36 % yield acetate), which is, however, lower than with 8 but yet significantly higher than the one observed with other simple ruthenium catalysts 14 and 15 (conversions <2%; Table 1, entries 6–7). The low performance of the rhodium amine catalysts 6 [40] and 16 [54] is especially noteworthy. In particular complex 6 , which is highly active in the reaction of higher alcohols with N 2 O to carboxylate derivatives and N 2 , shows poor performance with ethanol as a substrate (only up to 41 % yield).…”
Section: Resultsmentioning
confidence: 99%
“…found that the diruthenium complex 5 was able to oxidise cyclooctanol at 150 °C, however a high catalyst loading (5 mol %) was used [39] . Up to date the most active catalyst for the oxidation of a wide range of higher primary alcohols by N 2 O to form carboxylic is complex 6 [40] . Quantitative yields of the dehydrogenative coupling products were achieved under mild conditions (T=50 °C, p=1 bar N 2 O) and with a low catalyst loading (1 mol %) (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Kinetically recalcitrant toward decomposition and reduction, [3] this gas is generally decomposed through catalytic activation at temperature above 400 °C with heterogeneous catalysts to provide oxygen and nitrogen, [4] sometimes with the combined use of simple reducing additives like methane, [5–7] carbon monoxide, [4] propane [8] or benzene [9,10] . A few homogeneous catalysts (ruthenium, rhenium, or rhodium complexes) have also been described for nitrous oxide reduction into nitrogen under moderated temperatures (rt to 50 °C) [11,12] …”
Section: Introductionmentioning
confidence: 99%